DAKWAH DIGITAL NAHDLATUL ULAMA DALAM MEMAHAMI NILAI-NILAI ASWAJA AN NAHDLIYYAH - Hesty Putri Utami, (Mediakita, 2020)
This study aims to analyze the Nahdlatul Ulama digital da'wah in understanding the aswaja An-Nahdliyyah values and find out whether or not the digital da'wah of Nahdlatul Ulama can provide understanding to the public related to Ahlussunah Wal Jama'ah An-Nahdliyah by posting the related contents through the Nahdlatul Ulama social media accounts. This research used a descriptivequalitative method with the mass communication theory. The data in this study were obtained from the Nahdlatul Ulama official accounts and literatures appropriate with the research context. The results showed that the Nahdlatul Ulama digital da'wah in understanding aswaja An-Nahdliyyah with the formation of Nahdlatul Ulama cyber team and management of Nahdlatul Ulama social media accounts was emphasized in accordance with the Aswaja AnNahdliyah concept based on Khittoh Nahdlatul Ulama as stated in the existing da'wah typology. Thus, it can be concluded that the Nahdlatul Ulama Digital da'wah is indeed used to provide understanding to public to behave in accordance with the Aswaja An-Nahdliyyah values.